PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS CANVA WEB PADA MATERI ANATOMI FISIOLOGI DI SMK NEGERI 1 POGALAN TRENGGALEK - Recsy Safa Pramesti; Dindy Sinta Megasari; M.A. Hanny Ferry Fernanda; Octaverina Kecvara Pritasari (Program Studi Pendidikan Tata Rias, 2026)
This study aims to evaluate how effective a web-based interactive learning medium built with Canva is when usedin Anatomy and Physiology lessons, while also examining students’ responses to it. The underlying issue arisesfrom students’ suboptimal learning achievement, which is attributed to the limited ability of conventional printedmaterials to depict the microscopic structure of the skin. The research adopts a Research and Development (R&D)method following the ADDIE procedure (Analysis, Design, Development, Implementation, and Evaluation). Theparticipants were 35 tenth-grade students from the “Skin and Hair Care” (TKKR) vocational program. Data weregathered using validation sheets from content, media, and language experts, supplemented by learning-outcometests (pre-test and post-test) and a student response questionnaire. The field findings indicate that this Canvabased interactive medium was rated “highly suitable” by all validators. Its impact is reflected in a significantincrease in students’ average cognitive scores, from 62.06 to 90.97, with an N-gain of 0.78 falling into the “high”category. All students (100%) responded positively, placing it in the “very good” category. Based on these results,this web-based learning medium is declared valid, effective, and practical for strengthening comprehension andcognitive achievement in Anatomy and Physiology